Techno-economic viability, environmental impact and development approaches for photovoltaic pumping system in Cagayan Valley Region - Balderama, O. F.; Velasco, R. D.; Lazaro, S. V.; Castro, A. J. (2008)
This paper presents R&D results on the viability, environmental impact and development approach on the adoption and commercialization of a solar powered pumping system for domestic uses under Cagayan Valley condition.
The research utilized the existing 24-unit photovoltaic installation with a submersible pump. Climatic data was collected from the nearby agrometeorological station jointly operated by PAGASA and Isabela State University. A water level recorder was used to measure drawdown during pumping test and standard electrical multi-meter was likewise used to monitor the amount of current and voltage generated by the PV system. The CROPWAT simulation model was utilize to benchmark existing climate condition in the study area to verify the suitability of PV-pumping system and in estimating crop and irrigation requirements.
Result of the study revealed that PV-pumping is most suitable from the month of December to April since crop water requirements far exceed available rainfall. The study also showed the high correlation on the relationship between solar radiation, discharge and voltage. Through this relationship, a regression model was established as a useful tool for further analysis and forecasting purposes.
Economic viability indicators manifested that the use of photovoltaic pumping system has proved to be sustainable. It is expected that after three and a half years the invested money is repaid and one can achieve a long-term profit within 20 years of its life-span. To further the promotion and commercialization of the technology, on-station and community pilot projects are being established.